Conception of Motion as Newton Law Implementation among Students of Physics Education - Eko Sujarwanto; Ino Angga Putra (Universitas Negeri Malang, 2019)
Abstract: This present research was conducted due to students difficulty found in explaining physis meaning of Newton Law although they are capable of writing its mathematical representation. Multiple choices of identification test on Newton Law regarding motion were given to students who are registered in Basic Mechanics and Physics I academic year 2016/2017. The analysis was based on student answers and the level of student confidence in the correctness of the answers in quantitative descriptive and qualitative. The results of the analysis of identification tests were reinforced by thinking map of Newton's laws of student presentation and followed up by interviews. The results of this study indicate that students' conceptions of motion and Newton's laws is limited. Prospective teacher students need to learn and comprehend the applied concepts of Motion and Newton's Law and influenced by common sense. Abstract: Penelitian dilakukan dengan memberikan tes identifikasi aplikasi hukum-hukum Newton tentang gerak kepada mahasiswa berupa soal pilihan ganda pada mahasiswa yang terdaftar pada matakuliah Mekanika dan Fisika Dasar I tahun akademik 2016/2017.Analisis didasarkan pada jawaban mahasiswa dan tingkat kepercayaan mahasiswa terhadap kebenaran jawabannya secara kuantitatif deskriptif dan kualitatif. Hasil analisis tes identifikasi diperkuat dengan thinking map hukum-hukum Newton sajian mahasiswa dan ditindaklanjuti dengan wawancara. Hasil penelitian ini menunjukkan bahwa konsepsi mahasiswa tentang gerak dan hukum-hukum Newton dalam kategori "Kurang Paham". Mahasiswa calon guru perlu belajar dan mempelajari konsep Gerak dan Hukum Newton secara aplikatif dan dipengaruhi oleh common sense